2021
DOI: 10.11121/ijocta.01.2021.00974
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of COVID-19

Abstract: Coronavirus disease of 2019 or COVID-19 (acronym for coronavirus disease 2019) is an emerging infectious disease caused by a strain of coronavirus called SARS-CoV-22, contagious with human-to-human transmission via respiratory droplets or by touching contaminated surfaces then touching them face. Faced with what the world lives, to define this problem, we have modeled it as an optimal control problem based on the models of William Ogilvy Kermack et Anderson Gray McKendrick, called SEIR model, modified by addin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Moussouni et al. [8] modeled an optimal control problem based on the models of William Ogilvy Kermack et Anderson Gray McKendrick, called the SEIR model, modified by adding compact-ments suitable for their study. Özköse et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moussouni et al. [8] modeled an optimal control problem based on the models of William Ogilvy Kermack et Anderson Gray McKendrick, called the SEIR model, modified by adding compact-ments suitable for their study. Özköse et al.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal strategy in scenarios that involve administration of vaccines, increased vaccine supply, and limited combinations of interventions [19][20][21][22][23]. Furthermore, the mathematical model is extended to the optimal control problem by including control variables in the model as surgical face masks, social distancing, selfisolation, sensitization and awareness of disease transmission, as well as control including reducing the cost infrastructure such as testing facilities, which can lead to detection fast cases infected with Covid [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transmission dynamics of echinococcosis and mumps virus and some treatment control strategies recommended for eradication of these diseases can be found in [26,27], respectively. Especially, recently, there are studies on optimal control of COVID-19 and its co-infection [28,29,30,31,32,33,34]. However, no studies have been found on the omicron variant in the literature review.…”
Section: Introductionmentioning
confidence: 99%